2002
DOI: 10.1101/gad.991102
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Ras1, dMyc, and dPI3K signaling in the developing Drosophila wing

Abstract: The Ras GTPase links extracellular signals to intracellular mechanisms that control cell growth, the cell cycle, and cell identity. An activated form of Drosophila Ras (Ras V12 ) promotes these processes in the developing wing, but the effector pathways involved are unclear. Here, we present evidence indicating that Ras V12 promotes cell growth and G 1 /S progression by increasing dMyc protein levels and activating dPI3K signaling, and that it does so via separate effector pathways. We also show that endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
152
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(173 citation statements)
references
References 78 publications
20
152
1
Order By: Relevance
“…In agreement with previous reports, we find that Ras V12 induces the PI3K pathway in Drosophila (Prober and Edgar, 2002). Yet curiously, Ras V12 , Dlg RNAi tumors exhibit low levels of PI3K signaling.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In agreement with previous reports, we find that Ras V12 induces the PI3K pathway in Drosophila (Prober and Edgar, 2002). Yet curiously, Ras V12 , Dlg RNAi tumors exhibit low levels of PI3K signaling.…”
Section: Discussionsupporting
confidence: 94%
“…This interpretation implies that the activation of PI3K through Ras V12 depends on proper cell polarity. In support of this explanation, Prober and Edgar (2002) reported that Ras V12 activates the PIP 3 reporter only at the apical side of cells. Additionally, studies have shown that PTEN directly binds to the polarity gene Bazooka and that the activity of the PI3K pathway is polarized in Drosophila oocyte cells (von Stein et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Interestingly, many of the Minute genes, as part of the large number of genes involved in ribosomal biogenesis, are dMyc transcriptional targets. Also, as mentioned above, dMyc expression is influenced by Wg and Dpp [19,21,51]. These observations might imply that all cell competition -competition involving dMyc, a reduction in ribosome biogenesis, or lack of patterning factors -operates by the same mechanism.…”
Section: A Competitive Edge: Dmyc Defines the Winnersmentioning
confidence: 77%